POLA ARUS DI KOLAM PASANG SURUT AKIBAT PENGARUH ANGIN - Achmad Rusdiansyah (INFO-TEKNIK, 2006)
The Characteristics of water quality in shallow water of the pool of the rise and fall of the tides depend on the movement of stream flow.  Thus, on the first stage is the analysis of stream pattern and velocity.  The stream in pool of the rise and fall of the tides is influenced by the tides movement, besides, it can happened because of the side effect of winds blow.  The influence of the winds blow with a velocity will give forces on the water surface such as shearing force, and for the result, it push the water mass so the stream movement happen, witch is stated in the continuity and momentum equations.The stream pattern flow and velocity result can be examined by making a two dimensional (2-D) hydrodynamic of numerical model. The model is based on the numerical solution of continuity and momentum equations, which are solved with finite different method, the explicit of Mac Cormack method.The validity of model is tested with model experiment, 1-D stream flow and 2-D stream flow simulations with rectangle stream pattern.  The experiment is done in the pool of the rice and fall of the tides.  The results of the study had given satisfactory result.